Possibilities of pathogenetic correction of hyperkinetic disorders taking into account an acid-base balance - Hertsev, V. N.; Stoyanov, A. N.; Muratova, T. N.; Vastyanov, R. S.; Kolesnik, E. A. (Journal of Education, Health and Sport, 2019)
As a result of analysis of the available scientific data, a significant relationship between hyperkinetic syndromes and changes in the acid-base state has been revealed. The provoking effect of alkalosis on the occurrence and severity of hyperkinetic disorders was confirmed. An own example of effective treatment of patient with essential myoclonus with taking in account his acid-base state has been given. The addition of acetylsalicylic acid to the treatment with clonazepam caused a more significant decrease in the severity of hyperkinetic disorders and improved the patient’s general condition and his quality of life. So that we suggest studying of acid-base balance in patients with hyperkinetic syndromes and syndrome of increased neuromuscular excitability in the outpatient setting and in hospital conditions at the making of initial diagnosis, and also recommend studying of acid-base balance in patients who already have neurological diagnoses, if such a study has not been made previously. Correction of acid-base status in the treatment of patients with hyperkinetic syndromes and the syndrome of increased neuromuscular excitability contributes to greater effectiveness of therapy than just symptomatic treatment of hyperkinetic disorders.